Trust management in mobile platforms - YAN, Zheng (Institutional Knowledge at Singapore Management University, 2017)
Mobile platform has become a mainstream computing platform that runs various applications useful in people's everyday life. Trust management plays an important role in mobile platform for providing a secure and dependable execution environment for mobile applications to support mobile services, mobile networking, and communications. This book chapter offers a comprehensive review on trust management in mobile platform. The content of this book chapter contains two parts. In the first part, we introduce the basic knowledge of trust, trust modeling, and trust management. The second part provides an overview on several fundamental technologies of trust management in mobile platform, such as trust evaluation on mobile applications, mobile trusted computing platform, and trust management on mobile software components, as well as mobile malware detection. Moreover, we discuss unsolved issues, specify research challenges and indicate future research trends.